Magnetic properties and Curie temperatures of disordered Heusler compounds: Co1+xFe2-xSi - Fischer, Julia Erika; Karel, Julie; Fabbrici, Simone; Adler, Peter; Ouardi, Siham; Fecher, Gerhard H.; Albertini, Franca; Felser, Claudia (Physical Review B, 2016)
The local atomic environments and magnetic properties were investigated for a series of Co1+xFe2-xSi (0≤x≤1) Heusler compounds. While the total magnetic moment in these compounds increases with the number of valance electrons, the highest Curie temperature (TC) in this series was found for Co1.5Fe1.5Si, with a TC of 1069 K (24 K higher than the well-known Co2FeSi). Fe57 Mössbauer spectroscopy was used to characterize the local atomic order and to estimate the Co and Fe magnetic moments. Consideration of the local magnetic moments and the exchange integrals is necessary to understand the trend in TC.
CRIS-Team Scopus Importer:2023-03-20